If cosecα, cotα are the roots of
then,
1) ![a^{4} + b^{4} + 4ab^{2}c = 0\\ a^{4} + b^{4} + 4ab^{2}c = 0\\](https://tex.z-dn.net/?f=a%5E%7B4%7D+%2B+b%5E%7B4%7D+%2B+4ab%5E%7B2%7Dc+%3D+0%5C%5C)
2) ![a^{4} - b^4 + 4ab^2c = 0 a^{4} - b^4 + 4ab^2c = 0](https://tex.z-dn.net/?f=a%5E%7B4%7D+-+b%5E4+%2B+4ab%5E2c+%3D+0)
3) ![a^2 - b^2 = 2ac a^2 - b^2 = 2ac](https://tex.z-dn.net/?f=a%5E2+-+b%5E2+%3D+2ac)
4) ![a^2 + b^2 - 2abc = 0 a^2 + b^2 - 2abc = 0](https://tex.z-dn.net/?f=a%5E2+%2B+b%5E2+-+2abc+%3D+0)
Be Honest and Explain your answer :)
Please don't spam your answer.
Answers
Answer:
Step-by-step explanation:
brainliest brainliest brainliest brainliest brainliest brainliest brainliest brainliest brainliest
![](https://hi-static.z-dn.net/files/d9c/a12983feb5768c8dda37c49cf378d9ee.jpg)
![](https://hi-static.z-dn.net/files/d82/76a8efde948d0299aecd0e9a4e7db8fa.jpg)
Answer:
Given quadratic equation,
a(b-c)x^2+b(c-a)^2+c(a-b)=0
also zeroes of given equation are equal.
Therefore,
discriminant=0
b^2-4ac=0
{b(c-a)}^2-4{a(b-c)}{c(a-b)}=0
b^2(c^2+a^2-2ac)-4{ab-ac}{ac-bc}=0
b^2c^2+a^2b^2-2ab^2c-4{a^2bc-ab^2c-a^2c^2+abc^2}=0
b^2c^2+a^2b^2-2ab^2c-4a^2bc+4ab^2c+4a^2c^2-4abc^2=0
b^2c^2+a^2b^2+2ab^2c-4a^2bc +4a^2c^2-4abc^2=0
b^2c^2+a^2b^2+4a^2c^2+2ab^2c -4a^2bc-4abc^2=0
We know that,
a^2+b^2+c^2+2ab+2bc+2ac={a+b+c}^
By above identity we get,
{bc+ab-2ac}^2=0
bc+ab-2ac=0
b(a+c)=2ac
l
b=2ac/(a+c)
l
Hence if zeroes of given quadratic
equation are equal then,
b=2ac/(a+c)
1/b = (a+c)/2ac
2/b = a/(ac) + c/ac
2/b = 1/c + 1/a
"1/a + 1/c = 2/b"__________proved
I think my answer is capable to clear your confusion..
Step-by-step explanation:
up